FILSAFAT ISLAM & TANTANGAN MODERNITAS (Menelaah Ulang Urgensi Filsafat Islam Dalam Konteks Modern) - Amin Ja’far Shadiq (KOLONI, 2026)
Islamic philosophy has developed since its inception to nowadays time. Unfortunately the stigma against philosophy in Islam is still often negative. Islamic philosophy is still identified with purely theological issues. This problem brought stagnation in developing Islamic philosophy further. This article aims to see how the relevance of Islamic philosophy in the modern context. This work finds that in genealogy Islamic philosophy has a character that is open to treasures from outside Islam, even though it is addressed critically and selectively. In addition, there are at least three areas of Islamic philosophy discourse, namely metaphysics, epistemology and ethics. In the modern context, with increasingly complex issues, a holistic and inseparable perspective is needed to face the challenges of the ever-changing modern world